Politeness Strategies in Classroom Interaction between Teacher and Students and among Students at Senior High School - Kristiani Lisma Vera Br Ginting; Arsen Nahum Pasaribu (Institut Agama Islam Negeri Palopo, 2023)
In classroom, politeness is needed to be applied to build a good relationship, good social interaction, and comfortable communication between teacher and students and avoid conflict which possibly happens. The purpose of this research is to know the types of politeness strategies used by students and teachers in classroom interaction and to describe the politeness strategies are realized in the teacher – student’s classroom interaction. This research are expected to be valuable for the teacher as the model in English teaching, the teacher can teach moral education in the teaching and learning process. Students will aware of the importance of politeness in English teaching and learning. The people who use polite language will be more honored and accepted in community. Polite in communication make conversation get closer between sepaker and hearer. There are four types of polieness strategies, there are Blad On Record, Positive Politeness Strategies, Negative Politeness Strategies and Off Recordthe researcher found the dominant strategy in teacher-students communication was Bald On Record Strategy which has 13 frequency (44,82%), and followed by Positive which has 10 fruquency (34,48%)In communication among students, the researcher found the most dominant politeness strategy used among students is positive politeness which has 21 frequency (46,66%) and followed by bald on record 17 frequency (37,77%).